Redesignability check for analog circuits with incomplete implementation information - WEY, C.-L; HUANG, W.-H (IEEE transactions on circuits and systems. 1, Fundamental theory and applications, 1999)
Reengineering of electronic circuits has received considerable interest in the design automation community. Reengineering is the examination and alternation of a system to reconstitute it in a new form, which potentially involves changes at the requirements, design, and implementation level. This paper deals with the redesign problem in which the original implementation information is either missing or incomplete. Given a target circuit with a set of test points and a set of missing components, a circuit is redesignable if the transfer function of each missing component can be derived from the partial knowledge in existing implementation. The derived transfer functions are then used to construct the missing components. This paper presents an efficient algorithm that checks if a target circuit is redesignable. A set of check rules is developed from circuit topology without the need of circuit simulations. Thus, the redesignability check process can be applied for both linear and nonlinear circuits.